Use of the multipurpose territorial cadaster on risk management - Amorim, Amilton (2009)
At first, this work presents a brief bibliographical review about records and risk management. After that, the methodology used on the execution of thematic maps through the Internet showing the characteristics of susceptible buildings to some type of risks is presented.Finally, it demonstrates the potential and viability of using this information on cadasters in this important area, while at the same time using minor financial resources.